2007
DOI: 10.1364/oe.15.006817
|View full text |Cite
|
Sign up to set email alerts
|

Free spectral range optimization of return-to-zero differential phase shift keyed demodulation in the presence of chromatic dispersion

Abstract: Optical differential phase shift keying is normally demodulated in a delay-line interferometer with a 1-bit delay such that the free-spectral-range of the demodulator is equal to the transmitted bitrate. We show using Karkunen-Loeve expansion simulation that free-spectral-range optimization leads to increased chromatic dispersion tolerances. The optimized delay inversely scales with the amount of chromatic dispersion such that a delay slightly shorter than the bit period increases tolerances with no adverse ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 14 publications
5
14
0
Order By: Relevance
“…This can be attributed to the difference in the sampling phase chosen in the two methods. In [10] it has been shown that due to the deterministic interference between consecutive symbols in the S-MZDI, the output is close to an inverted return-to-zero (RZ) signal. Because the realtime MLSE is optimized for NRZ-OOK modulation, it samples the signal in a different part of the symbol period resulting in our setup in a non optimal back-to-back performance, as explained in Fig.…”
Section: Real-time Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be attributed to the difference in the sampling phase chosen in the two methods. In [10] it has been shown that due to the deterministic interference between consecutive symbols in the S-MZDI, the output is close to an inverted return-to-zero (RZ) signal. Because the realtime MLSE is optimized for NRZ-OOK modulation, it samples the signal in a different part of the symbol period resulting in our setup in a non optimal back-to-back performance, as explained in Fig.…”
Section: Real-time Experimental Resultsmentioning
confidence: 99%
“…In this paper we present a simpler approach that results in a larger CD tolerance. We show that the use of a Mach-Zehnder delay interferometer (MZDI) with a <1-bit delay [8][9][10], together with MLSE, results in a ~4000 ps/nm CD tolerance for 10.7-Gb/s NRZ-DPSK modulation. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In [24] and [25], it has been shown that using an MZDI with a delay of less that between both arms for demodulating the DPSK signal can considerably enhance the CD tolerance. In [12] and [13], we extended this concept by applying an MLSE to the balanced output of the S-MZDI, and showed that this can enable a CD tolerance of up to 4000 ps/nm at 2-dB OSNR penalty.…”
Section: Conventional Mlse Combined With An S-mzdimentioning
confidence: 99%
“…The effects noted for NRZ-DPSK in [2], particularly with no dispersion, have a different origin to those reported here and were in fact caused primarily by the NRZ signal being partially converted to RZ. In another paper, [3], the effects of dispersion and PMD on RZ-DPSK were investigated with partial delay demodulation of the signal. In [3] a limited (12.5%) increase in dispersion tolerance was shown, in this paper we show that further optimization can lead to up to a 100% increase in dispersion tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…In another paper, [3], the effects of dispersion and PMD on RZ-DPSK were investigated with partial delay demodulation of the signal. In [3] a limited (12.5%) increase in dispersion tolerance was shown, in this paper we show that further optimization can lead to up to a 100% increase in dispersion tolerance. In particular we find that to gain the full benefit from partial DPSK it is essential to use the correct filter bandwidth, and that this bandwidth is narrower than the typical values used elsewhere.…”
Section: Introductionmentioning
confidence: 99%